Physical Attractiveness Interpersonal and Intrapersonal Variability of Assessments - Strzałko, Jan; Kaszycka, Katarzyna (Anthropological Review, 2022)
On the basis of face photographs, a team of 50 male judges assessed the physical attractiveness of 64 young women. The consistency of the opinions of the judges was investigated in reference to the attractiveness of the persons being assessed, the relationship of the assessments with morphological facial features – both of the persons being assessed and the observers, and the mutual similarity of the persons defined by the given judge as attractive. The discussion refers to sociobiological problems.